Antibacterial Activity of Leucaena leucocephala Leaf Extract Ointment against Staphylococcus aureus and Staphylococcus epidermidis - Tunik Saptawati; Novita Dwi Dahliyanti; Pradika Nudya Risalati Rachman (Universitas Ahmad Dahlan, 2019)
Practical experience shows that Leucaena leucocephala has long been used as a medicinal plant. The finely ground, crushed, or chewed leaves of this shrub are applied to the wound. This study aimed to determine the antibacterial activity of L. leucocephala leaf extract ointment against Staphylococcus aureus and Staphylococcus epidermidis. The extract was made by macerating L. leucocephala leaf powder in ethanol 70% with 10% concentration. The research samples included seven (7) formulas of ointments with various L. leucocephala leaf extract (LLE) concentrations, namely F1 (0%), F2 (5%), F3 (10%), F4 (15%), F5 (20%), F6 (25%), and F7(100%). Their antibacterial activities were measured from the diameter of the inhibition zone, which was formed because the administered antibiotics stopped the growth of S. aureus and S. epidermidis placed in Nutrient Agar medium. Gentamicin Sulfate ointment and Oxytetracycline HCl ointment were used as positive controls. The results showed that LLE inhibited the growth of S. aureus and S. epidermidis when prepared at concentrations of at least 20% (F5) and 25% (F6), respectively. The difference between the antibacterial activities of LLE 100% and Gentamicin Sulfate ointment was not significant. The capacities of LLE to prevent the growth of S. aureus and S. epidermidis were lower than Oxytetracycline ointment. These capacities express the antibacterial activity of LLE ointment against S. aureus and S. epidermidis, meaning that LLE can be used as a topical antibacterial agent.Â